Causal effects of gut microbiota on the risk of chronic kidney disease: a Mendelian randomization study - Luo, Mingli; Cai, Jiahao; Luo, Shulu; Hong, Xiaosi; Xu, Lingxin; Lin, Honghong; Chen, Xiong; Fu, Wen (Frontiers in Cellular and Infection Microbiology, 2023)
Background Previous studies have reported that gut microbiota is associated with an increased risk of chronic kidney disease (CKD) progression. However, whether gut microbiota has a causal effect on the development of CKD has not been revealed. Thus, we aimed to analyze the potential causal effect of gut microbiota on the risk of CKD using mendelian randomization (MR) study. Materials and Methods Independent single nucleotide polymorphisms closely associated with 196 gut bacterial taxa (N = 18340) were identified as instrumental variables. Two-sample MR was performed to evaluate the causal effect of gut microbiota on CKD (N = 480698), including inverse-variance-weighted (IVW) method, weighted median method, MR-Egger, mode-based estimation and MR-PRESSO. The robustness of the estimation was tested by a series of sensitivity analyses including Cochran’s Q test, MR-Egger intercept analysis, leave-one-out analysis and funnel plot. Statistical powers were also calculated. Results The genetically predicted higher abundance of order Desulfovibrionales was causally associated with an increased risk of CKD (odds ratio = 1.15, 95% confidence interval: 1.05-1.26; p = 0.0026). Besides, we also detected potential causalities between nine other taxa (Eubacterium eligens group, Desulfovibrionaceae, Ruminococcaceae UCG-002, Deltaproteobacteria, Lachnospiraceae UCG-010, Senegalimassilia, Peptostreptococcaceae, Alcaligenaceae and Ruminococcus torques group) and CKD (p < 0.05). No heterogeneity or pleiotropy was detected for significant estimates. Conclusion We found that Desulfovibrionales and nine other taxa are associated with CKD, thus confirming that gut microbiota plays an important role in the pathogenesis of CKD. Our work also provides new potential indicators and targets for screening and prevention of CKD.